SPFH1 and SPFH2 mediate the ubiquitination and degradation of inositol 1,4,5-trisphosphate receptors in muscarinic receptor-expressing HeLa cells. - Wang, Y; Pearce, M; Sliter, D; Olzmann, J; Christianson, J; Kopito, R; Boeckmann, S; Gagen, C; Leichner, G; Roitelman, J; Wojcikiewicz, R (2009)
Inositol 1,4,5-trisphosphate (IP(3)) receptors are endoplasmic reticulum (ER) membrane calcium channels that, upon activation, become substrates for the ER-associated degradation (ERAD) pathway. While it is clear that IP(3) receptors are polyubiquitinated and are transferred to the proteasome by a p97-based complex, currently very little is known about the proteins that initially select activated IP(3) receptors for ERAD. Here, we have transfected HeLa cells to stably express m3 muscarinic receptors to allow for the study of IP(3) receptor ERAD in this cell type, and show that IP(3) receptors are polyubiquitinated and then degraded by the proteasome in response to carbachol, a muscarinic agonist. In seeking to identify proteins that mediate IP(3) receptor ERAD we found that both SPFH1 and SPFH2 (also known as erlin 1 and erlin 2), which exist as a hetero-oligomeric complex, rapidly associate with IP(3) receptors in a manner that precedes polyubiquitination and the association of p97. Suppression of SPFH1 and SPFH2 expression by RNA interference markedly inhibited carbachol-induced IP(3) receptor polyubiquitination and degradation, but did not affect carbachol-induced calcium mobilization or IkappaBalpha processing, indicating that the SPFH1/2 complex is a key player in IP(3) receptor ERAD, acting at a step after IP(3) receptor activation, but prior to IP(3) receptor polyubiquitination. Suppression of SPFH1 and SPFH2 expression had only slight effects on the turnover of some exogenous model ERAD substrates, and had no effect on sterol-induced ERAD of endogenous 3-hydroxy-3-methylglutaryl-CoA reductase. Overall, these studies show that m3 receptor-expressing HeLa cells are a valuable system for studying IP(3) receptor ERAD, and suggest that the SPFH1/2 complex is a factor that selectively mediates the ERAD of activated IP(3) receptors.